1993
DOI: 10.1007/bf01244980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ageing on tissue levels of amino acids involved in the nitric oxide pathway in rat brain

Abstract: Nitric oxide (NO) and citrulline are produced from L-arginine by the action of NO synthase after activation of excitatory amino acid receptors. In addition to its role in neurodegeneration, there is convincing evidence that NO is also involved in long-term potentiation, a cellular analog of learning and memory in the mammalian nervous system. In the present study, concentrations of L-arginine, citrulline, aspartic acid and glutamic acid were determined in various brain regions of young and old rats. The aim wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…To rule out the contribution of pressor effects of this compound, further studies should be performed using more specific neuronal NOS inhibitors that do not have pressor effects. An interesting finding in the present study was that the intraperitoneal injection as well as the direct infusion of L-Arg into the cerebellum through a dialysis probe produced a persistent increase in NO2 and NO3 -levels, although it has been suggested that NOS may be saturated with L-Arg in the brain because L-Arg levels in the brain are far above the Km value of NOS for L-Arg (Strolin Benedetti et a!., 1993). It has been shown that L-Arg is predominantly located in the glial cells in the brain (Aoki et al, 1991) and that the release of L-Arg occurs after electrical white matter stimulation in rat cerebellar slices in vitro (Hansel et a!., 1992) and in the thalamus after physiological stimulation of afferents in vivo (Do et al, 1994).…”
Section: Role Of Extracellular Calcium In the Modulation Of No2 -And mentioning
confidence: 59%
“…To rule out the contribution of pressor effects of this compound, further studies should be performed using more specific neuronal NOS inhibitors that do not have pressor effects. An interesting finding in the present study was that the intraperitoneal injection as well as the direct infusion of L-Arg into the cerebellum through a dialysis probe produced a persistent increase in NO2 and NO3 -levels, although it has been suggested that NOS may be saturated with L-Arg in the brain because L-Arg levels in the brain are far above the Km value of NOS for L-Arg (Strolin Benedetti et a!., 1993). It has been shown that L-Arg is predominantly located in the glial cells in the brain (Aoki et al, 1991) and that the release of L-Arg occurs after electrical white matter stimulation in rat cerebellar slices in vitro (Hansel et a!., 1992) and in the thalamus after physiological stimulation of afferents in vivo (Do et al, 1994).…”
Section: Role Of Extracellular Calcium In the Modulation Of No2 -And mentioning
confidence: 59%
“…We postulate that the delay of the clinical manifestation in our elderly male patient was due to the endothelial damage and atherosclerosis caused by chronic hypertension. There have been reports of a decline in the nitric oxide (NO) precursors such as aspartic acid, citrulline, and arginine as well as an age-dependent decrease in endotheliumdependent relaxation, which is thought to be mediated by NO [22]. This led to subacute reperfusion to the compressed spinal cord area, resulting to this late-onset case of WCS.…”
Section: Discussionmentioning
confidence: 98%
“…Multiple factors could contribute to altered cerebral blood-flow regulation in the aged brain. For example, endothelial cell nitric oxide (NO) production and the subsequent regulation of vascular tone are reduced in the vasculature of the aged brain (6,11,38). Moreover, decreased NO also enhances PMN adhesion to the cerebral microcirculation after I-R (18,27,48).…”
Section: Discussionmentioning
confidence: 99%